A literary study of rasa tantra sar va siddha prayog samgraha with special reference to Pramehahara Yogas - Vrinda; Bhat Sulochana; Nagarajan Kavya; Anand Sharada (Wolters Kluwer Medknow Publications, 2023)
Objective: To critically review all formulations indicated for different types of Prameha with the objective of understanding the drug action and focusing on new drugs which could be more beneficial against diabetes. Data Source: Two volumes of preprinted versions of RTSVSPS, internet sources, and catalogs of various pharmaceutical companies were scrutinized. Review Methods: All the formulations of Pramehahara Yogas were compiled and classified as herbal-, herbo-mineral-, and mineral-based medicine. Related published works on DM were noted and all formulations were analyzed in various aspects such as type of ingredients used, research works, market available formulations, and commonly used Rasa dravya. Results: RTSVSPS treatise contains 1307 formulations out of which 104 medicines were indicated for diabetes. Fifteen compound drugs have published research work and only 62% are available in the market. Lauha bhasma is the most extensively used Rasa dravya. Conclusion: This article throws light on various unfathomed formulations and highlights. appropraite usage of compounds with different anupanas (vehicles) according to different conditions.